2016
DOI: 10.1039/c5cs00336a
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and classical dynamics of reactive scattering of H2 from metal surfaces

Abstract: We review the state-of-the art in dynamics calculations on the reactive scattering of H2 from metal surfaces, which is an important model system of an elementary reaction that is relevant to heterogeneous catalysis. In many applications, quantum dynamics and classical trajectory calculations are performed within the Born-Oppenheimer static surface model. However, ab initio molecular dynamics (AIMD) is finding increased use in applications aimed at modeling the effect of surface phonons on the dynamics. Molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
186
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 364 publications
(1,515 reference statements)
5
186
0
Order By: Relevance
“…In a recent study using double resonance excitation by RAP, Hundt et al (52) measured different efficacies for the three different symmetry components of the 2ν 3 overtone for CH 4 dissociation on Pt (111). The authors attributed the observed mode specificity to different degrees of C-H stretch vibrational amplitude localization in the dissociating bond (75).…”
Section: Mode Specificitymentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study using double resonance excitation by RAP, Hundt et al (52) measured different efficacies for the three different symmetry components of the 2ν 3 overtone for CH 4 dissociation on Pt (111). The authors attributed the observed mode specificity to different degrees of C-H stretch vibrational amplitude localization in the dissociating bond (75).…”
Section: Mode Specificitymentioning
confidence: 99%
“…All these results demonstrate that the intramolecular vibrational energy redistribution (IVR) in the reactant molecule is slow on the several-hundred-femtosecond timescale of the reactive collision (76), in contradiction with the basic assumption of fast and complete IVR made by statistical rate theories (77-80). Killelea et al (81) were the first to demonstrate vibrational bond selectivity in the dissociative chemisorption of methane on Ni (111). They showed that excitation of the C-H stretch fundamental ν 1 in CHD 3 results in a C-H:C-D cleavage branching ratio greater than 30:1.…”
Section: Mode Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Six-dimensional quantum dynamics has already become a standard tool to study diatomic molecule/surface interactions at low incidence energy(<2 eV), from reactive scattering [20][21][22][23][24] to molecular diffraction [24][25][26]. However, its accuracy in reproducing experimental data, disregarding phonons * cristina.diaz@uam.es and electron-hole pair excitations effects, relies on the accuracy of the underlying potential energy surface (PES) on which the dynamics is carried out [23,27].…”
Section: Introductionmentioning
confidence: 99%